Recognition of Lynch Syndrome Amongst Newly Diagnosed Colorectal Cancers at St. Paul's Hospital. (2nd July 2017) - Pi, Steven; Nap-Hill, Estello; Telford, Jennifer; Enns, Robert
Abstract : Background . Lynch Syndrome (LS) is the most common cause of inherited colorectal cancer (CRC). In British Columbia, most centres still use clinical criteria (Amsterdam II, Revised Bethesda, or the BC Cancer Agency's criteria) to determine who should undergo further first-line testing in the form of microsatellite instability or immunohistochemistry staining. Given the limitations with this strategy, LS is thought to be underrecognized. Objective . To investigate whether LS is truly underrecognized when compared to the reported prevalence. Methods . A retrospective chart review of all CRC cases diagnosed at St. Paul's Hospital from 2010 to 2013 was conducted. Results . 246 patients met inclusion criteria. 76% (83/109) with a family history of malignancy were unable to recall the specific malignancy or age of diagnosis. 18% (43/235) were only asked about a history of gastrointestinal related malignancy and 26% (65/246) met at least one of the three criteria but only 21% (13/63) received further investigation. Only 1.6% (4/246) had LS compared to the reported prevalence of 2–5% of all CRC cases. Conclusion . This data supports our hypothesis that LS is underrecognized. Issues at the patient, physician, and systems level need to be evaluated to determine where the limitations preventing appropriate testing are occurring.